Chronic reparative changes in medium-sized vessels in a case of primary cutaneous anaplastic large-cell lymphoma with angioinvasive features and cytotoxic phenotype: new histopathological findings in line with indolent clinical behavior - Macarenco, Ricardo S.; Oliveira, Deilson Elgui de [UNESP] (Lippincott Williams &wilkins, 2015)
Angioinvasion/angiodestruction has been reported in a small subset of primary cutaneous anaplastic large-cell lymphomas (PCALCL). Recently, PCALCL with angioinvasive features and cytotoxic phenotype has been characterized as a variant associated with good clinical outcomes despite worrisome histopathologic features. We report a case of PCALCL with angioinvasive features and cytotoxic phenotype associated with reparative changes on the wall of medium-sized vessels involved by the neoplasm, including intimal fibroblastic proliferation and luminal obliteration. This vascular pattern, although previously unreported in PCALCL, is in accordance with the indolent behavior observed in this entity and provides a further link with lymphomatoid papulosis type E.
Keywords: Primary cutaneous anaplastic large-cell lymphoma; CD30(+) lymphoproliferative disorder; Angiocentric lymphoma; Angioinvasive lymphoma; Cutaneous lymphoma; Cytotoxic phenotype; Endarteritis obliterans; Pseudovasculitis; Angiodestructive; Angioinvasive; Muscular vessels; Medium-sized vessels